Analisis Pengeluaran Pemerintah Di Sektor Subsidi Dan Pendidikan: Tidak Ada Hubungan Langsung Dengan Kemiskinan - Suwardi, Wisda Zulaeha; Islamiah, Nurhidayati (Jurnal Online Manajemen ELPEI, 2024)
The aim of this research is to determine the effect of government spending in the subsidy sector, education levels on poverty in Indonesia in 2017-2023. The research method used in this research is a quantitative study with a regression analysis approach, using secondary data from various sources such as the Central Statistics Agency (BPS), the Ministry of Finance, and Bank Indonesia. Data were analyzed using statistical techniques. The research results show that government spending in the field of subsidies has a negative relationship with poverty, but this relationship is not significant. Because the resulting data is not significant, the data cannot be continued with linear regression analysis. Education funding has a weak relationship with poverty, although this relationship is not significant. Because the resulting data is not significant, the data cannot be continued with linear regression analysis